Removal of heavy metals (Cd2+, cu2+, ni2+, pb2+) from aqueous solution using hizikia fusiformis as an algae-based bioadsorbent - Pham, Bich Ngoc; Kang, Jin Kyu; Lee, Chang Gu; Park, Seong Jik (Applied Sciences (Switzerland), 2021)
This study investigated the applicability of algae (Hizikia fusiformis, Green gracilaria, and Codium fragile) for removing heavy metals (Cd2+, Cu2+, Ni2+, and Pb2+) from aqueous solutions. Among the algae, H. fusiformis was chosen as a bioadsorbent and modified with NaOH and HCl. The results showed that the biosorption capacity of H. fusiformis improved significantly after treatment with NaOH; however, H. fusiformis modified with HCl did not achieve the expected value. The NaOH treatment enhanced the biosorption of metals on the treated H. fusiformis because of the hydrolysis reaction producing carboxylic (–COOH) and hydroxyl groups (–OH). The kinetics for Cd2+, Cu2+, Ni2+, and Pb2+ biosorption well fitted to pseudo-first-order, pseudo-second-order, and Elovich models, with R2 of >0.994. The Freundlich model provided a good fit for the equilibrium biosorption of Cd2+, Cu2+, and Ni2+ by both algae and the Langmuir model for Pb2+. The maximum biosorption of metals was in the order Pb2+ >> Cu2+ ≈ Ni2+ > Cd2+, with qmax of 167.73, 45.09, 44.38, and 42.08 mg/g, respectively. With an increase in the solution pH, metal biosorption was enhanced, and considerable enhancement was observed in the pH range of 2–4. Thus, H. fusiformis is expected to be considered a superior candidate for metal biosorption.
Keywords: Algae; Biosorption; Heavy metals; Hizikia fusiformis; Modification